2016
DOI: 10.1007/s10439-016-1594-6
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Tissue Engineering Using Gingival Mesenchymal Stem Cells Encapsulated in Alginate Hydrogels Containing Multiple Growth Factors

Abstract: Repair and regeneration of muscle tissue following traumatic injuries or muscle diseases often presents a challenging clinical situation. If a significant amount of tissue is lost the native regenerative potential of skeletal muscle will not be able to grow to fill the defect site completely. Dental-derived mesenchymal stem cells (MSCs) in combination with appropriate scaffold material, present an advantageous alternative therapeutic option for muscle tissue engineering in comparison to current treatment modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 54 publications
(74 reference statements)
3
68
0
Order By: Relevance
“…Our group and others 6470 have confirmed that alginate hydrogel scaffold can be considered as a promising encapsulating biomaterial for dental- and orofacial-derived MSCs, including GMSCs and PDLSCs (Fig. 2).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our group and others 6470 have confirmed that alginate hydrogel scaffold can be considered as a promising encapsulating biomaterial for dental- and orofacial-derived MSCs, including GMSCs and PDLSCs (Fig. 2).…”
Section: Introductionsupporting
confidence: 61%
“…More recently, Ansari et al 70 confirmed that GMSCs, when encapsulated in an alginate hydrogel microencapsulation system with multiple growth factor delivery capacity (loaded with myogenic growth factors), can be used in the repair and regeneration of muscular tissues.…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, the expression level of myogenic-related genes (MyoG, MyoD and Myf5) in GMSCs encapsulated in alginate hydrogel was higher than in GMSCs that were not encapsulated. Most importantly, during in vivo trails, the formation of small islands of muscle-like structures was observed eight weeks following subcutaneous transplantation of GMSCs in microspheres into immunocompromised mice figure 4b [74].…”
Section: Delivery Of Cells and Bioactive Moleculesmentioning
confidence: 99%
“…For example, alginate is a naturally occurring linear polysaccharide typically derived from brown seaweed that has been widely used as a hydrogel for tissue engineering and cell encapsulation applications due to its favourable properties including low toxicity, high biocompatibility and ease of gelation [107]. Possessing a porous microstructure allowing the diffusion of oxygen, nutrients and growth factors makes this material highly suitable as a scaffold for the growth and differentiation of myogenic cells in mass culture and for myoblast engraftment in skeletal muscle regeneration [33,74]. Among the natural hydrogels, those derived from decellularized extracellular matrix (ECM) have gained much attention due to their ability to conform to irregular shapes and the inherent bioactivity of the matrix source.…”
Section: Hydrogel Biomaterialsmentioning
confidence: 99%
“…The concept of combining the stem cells, growth factors and scaffold was demonstrated to be efficient for regeneration of bone [1,2] , cartilage [3] , muscle [4] , tendon [5] and nerve [6] . Most of these studies was conducted at in vitro and in vivo level, supposing that will perform the same efficiency when be applied in the clinical cases.…”
Section: Editorialmentioning
confidence: 99%